Comparison of SARS-CoV-2 Variants of Concern Alpha (B.1.1.7) vs. Beta (B.1.351) in Critically Ill Patients: A Multicenter Cohort Study - Louis, Guillaume; Belveyre, Thibaut; Goetz, Christophe; Gibot, Sébastien; Dunand, Paul; Conrad, Marie; Gaci, Rostane; Gette, Sébastien; Ouamara, Nadia; Perez, Pascale; Cadoz, Cyril; Picard, Yoann; et al. (Frontiers in Medicine, 2022)
Objectives: The clinical outcomes of the Beta (B.1.351) variant of concern (VOC) of the SARS-CoV-2 virus remain poorly understood. In early 2021, northeastern France experienced an outbreak of Beta that was not observed elsewhere. This outbreak slightly preceded and then overlapped with a second outbreak of the better understood VOC Alpha (B.1.1.7) in the region. This situation allowed us to contemporaneously compare Alpha and Beta in terms of the characteristics, management, and outcomes of critically ill patients. Methods: A multicenter prospective cohort study was conducted on all consecutive adult patients who had laboratory confirmed SARS CoV-2 infection, underwent variant screening, and were admitted to one of four intensive care units (ICU) for acute respiratory failure between January 9th and May 15th 2021. Primary outcome was 60-day mortality. Differences between Alpha and Beta in terms of other outcomes, patient variables, management, and vaccination characteristics were also explored by univariate analysis. The factors that associated with 60-day death in Alpha- and Beta-infected patients were examined with logistic regression analysis. Results: In total, 333 patients (median age, 63 years; 68% male) were enrolled. Of these, 174 and 159 had Alpha and Beta, respectively. The two groups did not differ significantly in terms of 60-day mortality (19% vs. 23%), 28-day mortality (17% vs. 20%), need for mechanical ventilation (60% vs. 61%), mechanical ventilation duration (14 vs. 15 days), other management variables, patient demographic variables, comorbidities, or clinical variables on ICU admission. The vast majority of patients were unvaccinated (94%). The remaining 18 patients had received a partial vaccine course and 2 were fully vaccinated. The vaccinated patients were equally likely to have Alpha and Beta. Conclusions: Beta did not differ from Alpha in terms of patient characteristics, management, or outcomes in critically ill patients.